DIFFERENTIAL DIAGNOSIS OF RESPIRATORY ALLERGOSIS AND ATYPICAL PNEUMONIA IN CO-INFECTIONS: CLINICAL, LABORATORY, AND IMMUNOLOGICAL INDICATORS (CAHIERS MAGELLANES-NS, 2024)
Abstract. Differentiating respiratory allergosis and atypical pneumonia in cases of co-infection presents significant diagnostic challenges due to overlapping clinical symptoms. This study evaluates 150 patients to identify clinical, laboratory, and immunological indicators that aid in their differentiation. Key findings highlight elevated eosinophil counts and allergen-specific IgE as markers for allergosis, while increased CRP, IL-6, and pathogen-specific PCR confirm pneumonia. ROC analysis demonstrated high diagnostic accuracy for these indicators, with composite AUC values exceeding 0.9. Comprehensive cytokine profiling and T-cell ratio analysis further improved diagnostic precision. The study emphasizes a multi-modal approach for accurate differentiation, optimizing treatment strategies for co-infected patients.